Disparity in Court Determinations on Interfaith Adoption: A Study on Legal Certainty in Judicial Practice - Saffana Ayu Azzahra; Hazar Kusmayanti; Sherly Machmud Imam Slamet (Dinasti Research, 2026)
The adoption of children of different religions in Indonesia has been normatively regulated under positive law; however, in judicial practice, discrepancies in court determinations are still found in cases involving similar legal facts. This is evident in the Determination of the Gianyar District Court Number 76/Pdt.P/2025/PN Gin and the Determination of the Banyumas District Court Number 9/Pdt.P/2018/PN Bms, where judges rendered differing decisions regarding applications for interfaith adoption. In one determination, the application was granted by taking into account customary law and the best interests of the child, whereas in the other determination, the application was rejected by emphasizing the requirement of religious conformity under positive law. This study aims to analyze the judges’ legal reasoning as well as the factors contributing to the disparity in determinations of interfaith adoption from the perspective of legal certainty theory. The research employs a normative legal method with statutory, case, and conceptual approaches. Legal materials are collected through library research and analyzed qualitatively. The results indicate that the disparity in determinations is caused by differences in judicial interpretation of the requirement of religious conformity, the application of the principle of the best interests of the child, and the influence of legal pluralism in judicial practice.